2007
DOI: 10.3748/wjg.13.6098
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic pancreas in the stomach: A case report and literature review

Abstract: Ectopic pancreas is defined as pancreatic tissue found outside the usual anatomic location of the pancreas. It is often an incidental finding and can be found at different sites in the gastrointestinal tract. It may become clinically evident when complicated by pathologic changes such as inflammation, bleeding, obstruction, and malignant transformation. In this report, a 40 years old woman with epigastric pain due to ectopic pancreatic tissue in the stomach is described. The difficulty of making an accurate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
86
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 4 publications
2
86
0
4
Order By: Relevance
“…Rare locations include the esophagus, the gallbladder, or the common bile duct. 11,14,15 Recently, Heller et al reported ectopic pancreatic tissue in the brain. 16 In our study, we focused on the duodenum; and after duodenectomy, heterotopic pancreatic tissue was found in 6% of cases.…”
Section: Discussionmentioning
confidence: 97%
“…Rare locations include the esophagus, the gallbladder, or the common bile duct. 11,14,15 Recently, Heller et al reported ectopic pancreatic tissue in the brain. 16 In our study, we focused on the duodenum; and after duodenectomy, heterotopic pancreatic tissue was found in 6% of cases.…”
Section: Discussionmentioning
confidence: 97%
“…These pancreatic rests are believed to arise during embryogenesis when the pancreas is formed from evaginations originating in the primitive duodenum. In autopsy series, the frequency of ectopic pancreas is between 1% and 2% [5]. The most common locations for ectopic pancreatic tissue are stomach, 25% to 38%; duodenum, 17% to 36%; jejunum, 15% to 22%, with the esophagus, gallbladder, common bile duct, spleen, mediastinum, fallopian tubes, and mesentery as rare locations [5].…”
Section: Discussionmentioning
confidence: 98%
“…Die häufigste Lokalisation dafür ist der Gastrointestinaltrakt, hier am häufigsten, wie bei unserem Patienten, das Magenantrum. Die Inzidenz in postoperativ untersuchten Magenresektaten wird in der Literatur mit 0,5-13,7% [1] angegeben, der Anteil der endoskopisch diagnostizierten Heterotopien ist deutlich geringer. In einem Untersuchungszeitraum von 7 Jahren zeigte sich an unserer Klinik bei 2 von 2000 Kindern endoskopisch heterotopes Pankreasgewebe.…”
Section: Diskussionunclassified
“…In einem Untersuchungszeitraum von 7 Jahren zeigte sich an unserer Klinik bei 2 von 2000 Kindern endoskopisch heterotopes Pankreasgewebe. Während dieses bei fehlenden gastrointestinalen Symptomen oft als Zufallsbefund ohne therapeutische Konsequenz gewertet wird, machen Symptome und Komplikationen wie therapieresistente Bauchschmerzen, Blutungen, (Magenausgangs)-Stenosen, Pankreatitiden und der Verdacht auf eine maligne Entartung u. U. ein operatives Eingreifen notwendig [1,2,3,4].…”
Section: Diskussionunclassified